Diagnostic Analysis of the Generative Mechanism of Extratropical Cyclones in the Northwest Pacific and Northwest Atlantic - Qinglong Gong; Yina Diao; Ruipeng Sun; Xuejun Xiong; Jilin Sun (Atmosphere, 2021)
We investigated the early-stage development of cyclones occurring in the strong baroclinic regions in the Northwest Pacific and the Northwest Atlantic based on European Center for Medium-range Weather Forecasts Re-Analysis-Interim (ERA-Interim) data. The composite background conditions corresponding to the cyclones on the onset day are characterized by upper troposphere divergence of westerly jet ahead of a trough, low troposphere convergence of westerly jet behind a trough, and strong meridional air temperature gradient (baroclinicity) both in the Northwest Pacific and the Northwest Atlantic, but with stronger baroclinicity in the Northwest Pacific. The composite velocity and temperature fields of the cyclone on the onset day show a clear horizontal front and a westward and northward vertical tilting of cyclonic circulation to the cold zone. The composite Northwest Pacific cyclone filed on the onset day has a warm core, whereas the composite Northwest Atlantic cyclone field has a cold core in the low troposphere. The leading adiabatic processes that contribute to the developing of the cold core cyclone in the Northwest Atlantic on the onset day is the temperature advection, while stronger vertical motion induces stronger adiabatic warming in the Northwest Pacific cyclones, which has a significant contribution to the development of warm core cyclones on the onset day.